The Effect of Variation in Number of Blades on Current and Voltage in Simple Waterwheel Props - Hakim, Marsa Raihanida; Setia Gandi, Ziyanti Putri; Zein, Nihayatu; Rahmah, Nurul Esa; Kusumah, Fuji Hernawati (Universitas Islam Negeri (UIN) Mataram, 2025)
The world's dependence on fossil fuels has caused energy crises and environmental pollution, making renewable energy a crucial solution to develop. This study aims to analyse the effect of blade number variation on current and voltage in a simple waterwheel system. A quantitative correlational design was used to measure the relationship between the number of blades and the resulting electric current and voltage. The experiment used an educational water turbine generator kit, a digital multimeter, a stopwatch, a beaker, and supporting tools. The procedure involved three stages: assembling the turbine kit, measuring current and voltage across four blade variations, and calculating water flow using a beaker and stopwatch. Blade variations tested were 8, 6, 4, and 2, with each configuration measured four times for accuracy. The results showed a direct correlation between the number of blades and the generated current and voltage. Reducing the blade count from 8 to 2 resulted in a 19.05% decrease in current (from 13.02 A to 10.54 A) and a 52.63% drop in voltage (from 0.38 V to 0.18 V). A key challenge during the experiment was the fluctuating water flow rate, which made it difficult to maintain a perfectly constant flow. Therefore, the flow rate was approximated using the discharge formula and considered relatively stable. This experiment confirms that increasing the number of blades enhances energy conversion efficiency. In conclusion, mechanical energy directly influences electrical output, with blade number being a key factor. Future studies should explore variations in blade design, materials, and water flow control for optimal micro-hydro efficiency.